Empowerment of Women-Owned Businesses through Islamic Financial Inclusion Instruments: The Role of Crowdfunding - Al Berto, Muhammad; Hamdun, Nabil Ghazy; Abror, Moh Arifal (FAKULTAS EKONOMI DAN BISNIS ISLAMMM, 2025)
Women entrepreneurs face financial constraints due to limited access to traditional banking, lack of collateral, and systemic biases. This study explores Sharia-compliant crowdfunding as an alternative financing model to enhance financial inclusion. Using a qualitative approach with library research, the study proposes a model integrating social intermediation (group formation, client appraisal, capacity building) and financial intermediation (qardh hasan for interest-free loans, musyarakah for investment-based financing). Findings suggest this approach can bridge the financing gap, promote women's economic participation, and create a more inclusive financial ecosystem. Expanding Islamic crowdfunding and financial literacy can further empower women entrepreneurs and drive sustainable economic growth.